2011
DOI: 10.1016/j.foodchem.2010.12.137
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds content and antioxidant activity in pomace from selected red grapes (Vitis vinifera L. and Vitis labrusca L.) widely produced in Brazil

Abstract: a b s t r a c tThe phenolic compounds content and antioxidant activity of pomace from the vinification of grape varieties widely produced in Brazil (Cabernet Sauvignon, Merlot, Bordeaux and Isabel) were investigated with a view to their exploitation as a potential source of natural antioxidants. Cabernet Sauvignon grape pomace was found to have the highest content of total phenolic compounds (74.75 mg gallic acid equivalent (GAE)/g), the highest antioxidant activity (determined using the 2,2 0 -azino-bis(3-eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

39
155
7
20

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(251 citation statements)
references
References 31 publications
39
155
7
20
Order By: Relevance
“…Since there are differences between various radical scavenging systems, different in vitro model systems have been recently recommended to evaluate antioxidant capacities (Rockenbach et al, 2011). Therefore, in this study, three model systems; β-carotene/linoleic acid, DPPH and reducing power through potassium ferricyanide methods were applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are differences between various radical scavenging systems, different in vitro model systems have been recently recommended to evaluate antioxidant capacities (Rockenbach et al, 2011). Therefore, in this study, three model systems; β-carotene/linoleic acid, DPPH and reducing power through potassium ferricyanide methods were applied.…”
Section: Resultsmentioning
confidence: 99%
“…As β-carotene loses its double bonds by oxidation development, its color also would disappear which can monitored by spectrophotometry. The presence of extracts with antioxidant activity can hinder β-carotene bleaching through neutralization of free radicals formed in the system (Kosar et al, 2011;Singh et al, 2002;Rockenbach et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Rockenbach et al 51 reported similar values for TPC (75.75 mg g db vars, growing environment, harvest time, winemaking conditions, storage conditions, extraction conditions, analytical method, etc.) affect the content of phenolic compounds in extracts.…”
mentioning
confidence: 87%
“…GP also contains substantial amount of non-digestible fiber (60%-70%), essential fatty acids (13%-19%), proteins (11%), as well as non-phenolic tocopherols, betacarotene, and minerals [6,7]. The polyphenolics from GP are known for their antioxidant and anti-inflammatory effects [8,9], which demonstrate preventive effects on cancer [10], cardiovascular diseases [11], and inflammatory bowel disease [12]. The GP polyphenolics have been used in food technology as antioxidants to inhibit the oxidation of fish lipids, frozen fish muscle, and fish oil [13].…”
Section: Introductionmentioning
confidence: 99%